Crustal structure in the Campanian region (Southern Apennines, Italy) from potential field modelling - Y. Kelemework (Nature Portfolio, 2021)
Abstract We present a 3D model of the main crustal boundaries beneath the Campanian region and the onshore and offshore surrounding areas, based on high-resolution potential field data. Our main objective is the definition of the main structural interfaces in the whole Campanian region from gravity and magnetic data, thanks to their ability to define them on a regional and continuous way. The complex morphology of the Mesozoic carbonate platform, which is fundamental to constrain the top of geothermal reservoir, was reconstructed by inverting the vertical gradient of gravity. We assumed local information from seismic models and boreholes to improve the model. We modeled the deep crustal structures by spectral analysis of Bouguer gravity and magnetic data. The inferred depth estimates indicate a shallow crystalline basement below the Tyrrhenian crust and the Apulian foreland and a significant depression beneath the Bradanic foredeep. The map of the Moho boundary shows a NE-SE verging trough below the Southern Apennine chain and two pronounced uplifts beneath the foreland and the Tyrrhenian crust. We also estimated the depth to the magnetic bottom, showing a thick magnetic crust below the mountain chain and shallow depths where the crustal heat flow is high. The models were compared with seismic sections along selected profiles; a good agreement was observed, despite of some inherent lower resolution for the gravity modelling from spectral methods. The regional covering and the continuity of our estimated crustal interfaces make it a new and valid reference for further geological, geophysical and geothermal studies, especially in areas such as northern and eastern Campania, where there is an incomplete geophysical and geological information.